Method of determining power and mathematical modeling of physical processes in testing traction induction motors by mutual loads - Viktor Vasilevich Kharlamov; Denis Igorevich Popov; Artyom Valerevich Litvinov (Вестник СибАДИ, 2017)
In this article suggested the method of determining power when testing traction induction motors and the mathematical model of tests updated by taking into account the power losses in uncontrolled rectifiers and controlled inverters included in the frequency converters. To refine the mathematical model proposed to use the method of determining the dependency of the losses in the elements of frequency converters, located in the structure of the scheme of mutual loads of induction motors, the magnitude of the consumed and generated power of test and load machine.